Behavior of Maternity Mothers in Choosing Dukuns as Birth Assistance in the Work Area of the Tanah Merah Health Center in 2022: Perilaku Ibu Bersalin Dalam Memilih Dukun Bayi Sebagai Tenaga Penolong Persalinan Di Wilayah Kerja Puskesmas Tanah Merah Tahun 2022 - Febi Zikriani; Agus Alamsyah; Riri Maharani; Miratu Megasari; Wulan Sari (Badnur Medisa Group, 2022)
Tanah Merah Village is one of the villages located in Indragiri Hilir district which is located in Tanah Merah District. Where the majority of the people are Muslim, and the majority of the work is fishing and trading. In Indragiri Hilir Regency, in Tanah Merah Village in 2019 there were 652 mothers giving birth and about 23.4% of mothers giving birth who were not assisted by Health Workers. In Sungai Batang Village, there were 259 mothers who gave birth and about 38.6% of mothers who gave birth were not assisted by health workers. In Concong Village, there were 283 mothers who gave birth, and about 49% of mothers who gave birth were not assisted by health workers. This study aims to determine the behavior of mothers in choosing traditional birth attendants as birth attendants in Tanah Merah Village. The variables studied were knowledge, attitudes, hereditary culture/traditions, affordability of health facilities, and husband/family support. Research informants consisted of mothers who had given birth at traditional birth attendants, mothers' families/husbands, traditional birth attendants, and midwives. This study uses a qualitative research type. Subject selection used a snowball technique with 5 main informants and 7 supporting informants. The results of this study The informant's knowledge about the dangers and risks of giving birth at a traditional birth attendant is still low, the attitude of the informant is comfortable if the birth is assisted by a traditional birth attendant, the culture of the informant chooses to give birth at a traditional birth attendant due to hereditary nature of the in-laws, the accessibility of health facilities is not too far but the mother prefers to give birth by TBAs because they can come home, The behavior of health workers who are not friendly in handling deliveries makes the informants reluctant to give birth at a health worker, Support from the mother's husband/family agrees to give birth at a traditional birth attendant.